DETECTION AND ASSESSMENT OF DISORDERS OF THE DEPRESSIVE SPECTRUM IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION DEPENDING ON THE METHOD OF TREATMENT - Kudria, I.P.; Shevchenko, T.I.; Voroshilova, T.A.; Tretiak, N.H.; Kryvoruchko, I.H.; Pushko O.О.; Shaposhnyk О.А. (World of Medicine and Biology, 2022)
The frequent combination of mental disorders of the depressive spectrum and cardiovascular diseases is one of the most urgent problems of modern medicine. The purpose of the study was to identify and assess, with the help of various psychodiagnostic methods, the degree of severity of depressive disorders in patients with acute myocardial infarction depending on the treatment method as a prerequisite for optimal drug therapy. 73 patients with the aforementioned pathology were studied and were divided into two groups. Group I included 44 patients who underwent urgent coronary angiography with subsequent stenting of the infarct-related coronary artery; Group II – included 29 patients who received only drug therapy. Examination of patients was carried out according to Ukrainian standards, in particular, a survey according to the scale of Beck and Zung. Patients with acute myocardial infarction after urgent coronary angiography with stenting of the infarct-dependent artery were more likely to have mild and moderate depression according to the Beck scale compared to patients who received only conservative medical treatment. The reverse pattern is observed for moderate and severe depression. 68.2% of patients with acute myocardial infarction after interventional intervention and 62.1% on the background of conservative treatment according to the Zung scale showed depression of various degrees of severity, mostly mild.